SISTEM FORMULA DAN FUNGSI DALAM SASTRA LISAN RONGGENG PASAMAN - Satya Gayatri (Jurnal Elektronik WACANA ETNIK, 2010)
Oral literature that has the values of local wisdom, but less desirable, especially on the younger generation. Oral literature is a cultural asset that has been abandoned by their owners. This is one of them caused by the impact of globalization that hit the Indonesian nation, so many lost literature that only a name. Along with the automatic player oral literature has a reduced or even lost. Therefore, it is necessary revitalization of the oral literature one formulaic system and the function of an oral literature to overcome the scarcity of players a show oral literature in society.The system is the use of iteration formula is implemented in a show. Formula made by players in conveying the text often is by repeating words, phrases, clauses, or array. Likewise, the frequency of carrying out automatic performance function of a show done and will anticipate the scarcity of players on an oral literary performances.